Measuring the welfare of sub-groups subject to premature mortality: The new welfare measures. Issue 9 (2nd September 2014) - Doessel, D.P.; F. Williams, Ruth
Abstract : Purpose: – The purpose of this paper is to provide an exposition of the concepts relevant to measuring the economic effect of premature mortality and the conception of how the social loss from premature mortality can be incorporated into social welfare measurement. None of the conventional welfare measures currently pick up this welfare signal. Design/methodology/approach: – Various concepts are examined in the conventional and "new" literatures of welfare measurement. Six Venn diagrams show how various concepts "fit together". Findings: – This paper outlines a framework for measuring the economic effect of premature mortality in a conceptually appropriate way. Thus the paper shows how the welfare loss associated with premature mortality can be incorporated into social welfare measurement. Research limitations/implications: – Accurate premature mortality measurement is difficult but this data problem hardly limits this exercise. Sensitivity analyses can alleviate this measurement problem. Practical implications: – The main practical implication is that empirical applications are feasible. Time series data can be analysed from this conceptual framework to determine whether the problem of the social loss from premature mortality is improving through time, or worsening. Social implications: – Knowing the size of the welfare impact of premature mortality is useful not only on policy fronts concerning premature mortality prevention. Originality/value: – "New welfare measurement" has not yet been applied to the notion of the social loss from premature mortality.